2020
DOI: 10.1186/s43093-020-00041-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning predictivity applied to consumer creditworthiness

Abstract: Credit risk evaluation has a relevant role to financial institutions, since lending may result in real and immediate losses. In particular, default prediction is one of the most challenging activities for managing credit risk. This study analyzes the adequacy of borrower’s classification models using a Brazilian bank’s loan database, and exploring machine learning techniques. We develop Support Vector Machine, Decision Trees, Bagging, AdaBoost and Random Forest models, and compare their predictive accuracy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Other authors also develop and compare different models for credit risk assessment: SVM, DTs, AdaBoost, RF, logistic regression, ANN, and XGBoost. Of these, the different models with greater predictive accuracy are obtained by each author: AdaBoost and RF [35], DT [36]- [40]. On the other hand, Putri et al [41] propose to analyze credit risk using SMV.…”
Section: Ai and ML Applications And Algorithms Proposed In The Bankin...mentioning
confidence: 99%
“…Other authors also develop and compare different models for credit risk assessment: SVM, DTs, AdaBoost, RF, logistic regression, ANN, and XGBoost. Of these, the different models with greater predictive accuracy are obtained by each author: AdaBoost and RF [35], DT [36]- [40]. On the other hand, Putri et al [41] propose to analyze credit risk using SMV.…”
Section: Ai and ML Applications And Algorithms Proposed In The Bankin...mentioning
confidence: 99%
“…The goals we delegate to AI are no longer inconsequential. They can be used to identify potential threats [46], [47], identify trends in seasonal influenza [48], [49], whether someone is a good job candidate [50], or determine a person's creditworthiness [51].…”
Section: B Fear and Loathing Of Autonomymentioning
confidence: 99%
“…Overall, these findings suggest that there is potential for businesses to develop default prediction models by experimenting with machine learning approaches. 8 This study focuses on using machine and deep learning models with real-world data to estimate loan default probability. The most significant features from multiple models are selected and used to compare the performance of Random Forest and decision tree classifiers.…”
Section: Literature Surveymentioning
confidence: 99%
“…The results indicated that AdaBoost and Random Forest performed better than other models, while SVM models performed poorly when using both linear and nonlinear kernels. Overall, these findings suggest that there is potential for businesses to develop default prediction models by experimenting with machine learning approaches 8 . This study focuses on using machine and deep learning models with real‐world data to estimate loan default probability.…”
Section: Literature Surveymentioning
confidence: 99%